Limestone Wedges: ad hoc Quarrying Tools of the Kaizer Hill Quarry Site. (2nd April 2020) - Novoselsky, Ira; Grosman, Leore; Herzlinger, Gadi; Goren-Inbar, Naama
ABSTRACT: Kaizer Hill is a Pre-Pottery Neolithic A flint and limestone quarry site situated in central Israel. During systematic collection and excavation at the site, a large quantity of limestone wedges was recovered. This study reports the results of a detailed morphological, technological and functional attribute analysis conducted on these artifacts. The results indicate that these artifacts were indeed utilized for the expansion of natural cracks and fissures in the bedrock, with the use of forceful blows for their insertion. While some consistent morphological traits can be identified, there is a high degree of variability in most aspects of their morphology, and it seems that minimal effort and planning were invested in their production. Nevertheless, although the Kaizer Hill wedges apparently conform to the definition of ad hoc tools, they played a crucial role in the quarrying conducted at the site.